Low dielectric resin composition, prepreg, laminate, wiring board and resin

A low dielectric resin composition with a styrene-modified oligomer and crosslinking agent addresses the balance of low dielectricity, loss tangent, and expansion coefficient, enhancing performance in high-frequency electronic devices.

JP2025007802APending Publication Date: 2025-01-17SUMITOMO BAKELITE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023109435
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing resin compositions struggle to achieve a balance between low dielectricity, low dielectric loss tangent, and low coefficient of linear expansion, as seen in Patent Documents 1 and 2.

Method used

A low dielectric resin composition is developed using a resin (A) with a specific structure, a crosslinking agent (B), and optionally an inorganic filler (C) and coumarone resin (D), which includes a styrene-modified oligomer with a tolyl skeleton and a rigid aromatic group, along with a crosslinking agent to enhance properties.

Benefits of technology

The composition achieves significantly improved low dielectricity, low dielectric loss tangent, and low coefficient of linear expansion, making it suitable for high-frequency electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007802000001_ABST
    Figure 2025007802000001_ABST
Patent Text Reader

Abstract

To provide a low dielectric resin composition that achieves sufficiently low linear expansion coefficients while ensuring low dielectric constants and low dielectric loss tangents.SOLUTION: A low dielectric resin composition comprises a resin (A) having repeating units including the structure represented by formula (1) (excluding polystyrene resin), and a cross-linking agent (B), wherein R1 represents either CH or C(CH3) and R2 represents either hydrogen or a methyl group, and * represents a bond.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a low dielectric resin composition, a prepreg, a laminate, a wiring board, and a resin. [Background technology]

[0002] In recent years, electronic devices such as tablet terminals and smartphones have become more and more sophisticated, and their signal speeds and operating frequencies have increased dramatically. Therefore, electronic devices used in high-frequency ranges are required to have high low dielectric properties, and there is an increasing demand for low dielectric constants and low dielectric loss tangents.

[0003] Therefore, research and development of materials with low relative dielectric constant and low dielectric loss tangent has been progressing. For example, Patent Document 1 discloses a curable resin composition containing a modified polyphenylene ether and a styrene-based elastomer having a specific structure in order to obtain a uniform cured product and to satisfy all of the requirements of sufficient Tg, low dielectric properties, and low linear expansion coefficient of the cured product. In addition, Patent Document 2 discloses a resin composition containing a bismaleimide compound having a specific structure in order to obtain a low dielectric loss tangent, a low linear expansion coefficient, and adhesiveness. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2023-34824 A [Patent Document 2] Patent Publication No. 2023-1060 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the resin compositions described in Patent Documents 1 and 2, there is room for improvement in terms of achieving both a low dielectric constant and a low dielectric loss tangent, and a low linear expansion coefficient. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to solve these problems and have found that by using a new resin having a specific structure, it is possible to achieve a low dielectric constant, a low dielectric tangent, and a low linear expansion coefficient at a higher level than ever before.

[0007] According to the present invention, the following low dielectric resin composition, prepreg, laminate, wiring board and resin are provided.

[0008] [1] A resin (A) (excluding polystyrene resins) having a repeating unit containing a structure represented by the following formula (1), A crosslinking agent (B); A low dielectric resin composition comprising: [ka] (In formula (1), R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and * represents a bond.) [2] The low dielectric resin composition according to [1], The resin (A) has a weight average molecular weight (Mw) of 200 to 10,000. [3] The low dielectric resin composition according to [1] or [2], A low dielectric resin composition, wherein the content of the resin (A) is 1.0% by mass to 30% by mass based on the total solid content mass of the low dielectric resin composition. [4] The low dielectric resin composition according to any one of [1] to [3], A low dielectric resin composition, wherein the resin (A) has any repeating unit selected from the following formulae (2-1) to (2-3). [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and m and n each represent an integer of 1 to 36.) [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and l represents an integer of 1 to 26.) [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and s represents an integer of 1 to 12.) [5] The low dielectric resin composition according to any one of [1] to [4], The low dielectric resin composition, wherein the crosslinking agent (B) is one or more selected from the group consisting of trialkenyl cyanurate compounds, polyfunctional vinyl compounds, vinylbenzyl compounds, polyfunctional maleimide compounds, and isocyanate compounds. [6] The low dielectric resin composition according to any one of [1] to [5], A low dielectric resin composition further comprising an inorganic filler (C). [7] The low dielectric resin composition according to any one of [1] to [6], A low dielectric resin composition, wherein the content of the inorganic filler (C) is 40% by mass to 85% by mass based on the total solid content mass of the low dielectric resin composition. [8] The low dielectric resin composition according to any one of [1] to [7], The low dielectric resin composition further comprises a coumarone resin (D). [9] A prepreg formed by impregnating a fiber base material with the low dielectric resin composition described in any one of [1] to [8].

[10] The prepreg according to [9], The prepreg, wherein the fiber base material is one or more types selected from a glass fiber base material, a polyamide resin fiber, a polyester resin fiber, a polyimide resin fiber, and a fluororesin fiber.

[11] A laminate comprising the prepreg according to [9] or

[10] , and a metal layer disposed on at least one surface of the prepreg.

[12] A wiring board using the prepreg described in any one of [9] to

[11] .

[13] A resin having a repeating unit containing the structure represented by the following formula (1) (excluding polystyrene resin). [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and * represents a bond.)

[14] The resin according to

[13] . The resin has an average weight molecular weight (Mw) of 200 to 10,000.

[15] The resin according to

[13] or

[14] , A resin having a repeating unit selected from the following formulae (2-1) to (2-3). [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and m and n each represent an integer of 1 to 36.) [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and l represents an integer of 1 to 26.) [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and s represents an integer of 1 to 12.) Effect of the Invention

[0009] According to the present invention, there is provided a low dielectric resin composition which can achieve both low dielectric property and low dielectric dissipation factor, and a low linear expansion coefficient at a higher level than ever before. [Brief description of the drawings]

[0010] [Figure 1] 1 is a 1H-NMR spectrum of a resin (A-1) synthesized in an example. [Diagram 2] 1 is an infrared absorption spectrum of a resin (A-1) synthesized in an example. [Diagram 3] 1 is a 1H-NMR spectrum of a resin (A-2) synthesized in an example. [Figure 4] 1 is an infrared absorption spectrum of a resin (A-2) synthesized in an example. [Diagram 5] 1 is a 1H-NMR spectrum of a resin (A-3) synthesized in an example. [Figure 6] 1 is an infrared absorption spectrum of a resin (A-3) synthesized in an example.

[0011] Hereinafter, an embodiment of the present invention will be described in detail. In this specification, the expression "a to b" in the explanation of a numerical range means from a to b, unless otherwise specified. For example, "1 to 5% by mass" means "1% by mass to 5% by mass."

[0012] <Low dielectric resin composition> The low dielectric resin composition of the present embodiment (hereinafter, also referred to simply as the "resin composition") contains a resin (A) (excluding polystyrene resin) having a repeating unit including a structure represented by the following formula (1), and a crosslinking agent (B). This allows both low dielectric constant and low dielectric tangent and a low linear expansion coefficient to be achieved. The details of the reason are not clear, but it is speculated as follows. Conventionally, in order to impart low dielectric properties, an aliphatic skeleton has been introduced into the base resin, but this tends to increase the linear expansion coefficient. In contrast, the resin (A) contained in the low dielectric resin composition of the present embodiment has a rigid aromatic group and a relatively short aliphatic group as shown in formula (1), and therefore it is speculated that good low dielectric properties can be obtained while keeping the linear expansion coefficient low.

[0013] [ka] (In formula (1), R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and * represents a bond.)

[0014] Hereinafter, each component contained in the low dielectric resin composition will be described.

[0015] Resin (A) The resin (A) is a styrene-modified oligomer having a tolyl skeleton, excluding polystyrene resins.

[0016] The resin (A) preferably has any repeating unit selected from the following formulae (2-1) to (2-3).

[0017] [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and m and n each represent an integer of 1 to 36.)

[0018] [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and l represents an integer of 1 to 26.)

[0019] [ka] (In the formula, R1 represents either CH or C(CH3), R2 represents either hydrogen or a methyl group, and s represents an integer of 1 to 12.)

[0020] The resin (A) has a weight average molecular weight (Mw) of preferably 200 to 10,000, more preferably 500 to 8,000, even more preferably 800 to 5,000, and particularly preferably 1,000 to 3,000. By setting the weight average molecular weight (Mw) of the resin (A) within the above numerical range, good low dielectric properties are easily obtained. The weight average molecular weight may be measured by a general molecular weight measurement method, and specifically, a value measured by GPC may be mentioned.

[0021] Next, a method for synthesizing the resin (A) will be described. The method for synthesizing resin (A) of this embodiment includes, for example, a step of first dissolving p-tolualdehyde (compound a1), an aromatic compound having an aromatic substituted phenol and / or ether skeleton (compound b1), an acid catalyst, and a co-catalyst in an organic solvent, followed by heating and reacting to obtain a tolyl-based phenolic resin (p) (step 1), and a step of reacting the tolyl-based phenolic resin (p) with chloromethylstyrene in the presence of an alkali catalyst and a phase transfer catalyst in an organic solvent to modify the hydroxyl groups with styrene (step 2).

[0022] (Process 1) First, p-tolualdehyde (compound a1), an aromatic substituted phenol and / or aromatic compound having an ether skeleton (compound b1), an acid catalyst, and a co-catalyst are dissolved in an organic solvent, and then heated and reacted to produce toluyl-based phenolic resin (p), which is an intermediate of resin (A).

[0023] In step 1, the heating temperature may be, for example, about 50° C. to 200° C., and the heating time may be, for example, 1 hour to 72 hours. It is more preferable to carry out solution polymerization after removing dissolved oxygen in the solvent by nitrogen bubbling.

[0024] The acid catalyst may be a mineral acid such as sulfuric acid or hydrochloric acid, an organic acid such as paratoluenesulfonic acid, or a Lewis acid such as boron trifluoride etherate, etc. Among these, at least one of them may be used. The acid catalyst can be used in an amount of 1 mol % to 1000 mol % based on (compound a1 and compound b1).

[0025] The co-catalyst is not particularly limited, but may include thiols, or carboxylic acids such as 3-mercaptopropionic acid, and the like. The co-catalyst can be used in an amount of 1 mol % to 10 mol % based on (compound a1 and compound b1).

[0026] The organic solvent may be ketone-based solvents, ether-based solvents, ester-based solvents, acyclic aliphatic alcohol-based solvents, aromatic solvents, etc., and one or more selected from these may be used. Specific examples of the organic solvent include cyclopentanone, heptanone, anisole, butanol, toluene, etc., and one or more selected from these may be used.

[0027] From the viewpoint of obtaining good thermosetting properties while obtaining low dielectric constant and low linear expansion coefficient, the molar ratio (b1 / a1) of compound a1 and compound b1 can be preferably 0.5 to 4, more preferably 1 to 3, and even more preferably 1 to 1.5. In addition, a molecular weight modifier can be used as necessary.

[0028] Compound b1 is an aromatic compound having an aromatic substituted phenol and / or ether skeleton, and examples thereof include one or more compounds selected from 4-phenoxyphenol, diphenyl ether, and 2-(2-hydroxyphenyl)benzoxazole.

[0029] (Process 2) Next, in an organic solvent, the tolyl-based phenolic resin (p) synthesized in step 1 is reacted with chloromethylstyrene in the presence of an alkali catalyst and a phase transfer catalyst to modify the hydroxyl groups of the tolyl-based phenolic resin (p) with styrene, thereby synthesizing the resin (A).

[0030] In step 2, the heating temperature can be, for example, about 50° C. to 120° C., and the heating time can be, for example, 1 hour to 10 hours.

[0031] The alkaline catalyst may include, for example, potassium carbonate (K2CO3), sodium carbonate (Na2CO3), potassium hydroxide (KOH), sodium hydroxide (NaOH), sodium bicarbonate (NaHCO3), sodium acetate, or a combination thereof.

[0032] Phase transfer catalysts include, for example, tetrabutylammonium salts.

[0033] The reaction solution containing the synthesized resin (A) is then added to an alcohol such as hexane or methanol to precipitate the resin (A) in the solution. The resin (A) is then filtered and washed with an alcohol such as hexane or methanol, and then dried to obtain the resin (A) of the present embodiment.

[0034] The content of resin (A) is preferably 1.0 mass % to 30 mass %, more preferably 2.0 mass % to 20 mass %, and even more preferably 5.0 mass % to 10 mass %, relative to the total solid content of the low dielectric resin composition. By setting the content of the resin (A) to be equal to or more than the above lower limit, it becomes easy to reduce the linear expansion coefficient. On the other hand, by setting the content of the resin (A) to the above upper limit or less, low dielectric properties can be easily obtained while maintaining a low linear expansion coefficient.

[0035] [Crosslinking agent (B)] The crosslinking agent (B) may be one capable of initiating or accelerating a crosslinking reaction. From the viewpoint of the crosslinking reaction, the crosslinking agent (B) preferably has an average of two or more carbon-carbon unsaturated double bonds or isocyanate groups (-N=C=O) per molecule. The crosslinking agent (B) may be composed of one type of compound or two or more types of compounds.

[0036] Examples of the crosslinking agent (B) include triallyl isocyanurate compounds such as triallyl isocyanurate (TAIC) and trimethallyl isocyanurate, triallyl cyanurate compounds such as triallyl cyanurate (TAC), polyfunctional methacrylate compounds having two or more methacrylic groups in the molecule, polyfunctional acrylate compounds having two or more acrylic groups in the molecule, polyfunctional vinyl compounds having two or more vinyl groups in the molecule such as polybutadiene-based elastomers and polybutadienes having functional groups, vinylbenzyl compounds such as divinylbenzene having a vinylbenzyl group in the molecule, polyfunctional maleimide compounds having two or more maleimide groups in the molecule such as 4,4'-bismaleimide diphenylmethane (excluding the maleimide compounds), and isocyanate compounds having one or more isocyanate groups (-N=C=O). These are used alone or in combination of two or more.

[0037] Examples of the functional group of the polybutadiene-based elastomer having the above-mentioned functional group include a vinyl group, an epoxy group, a carboxy group, a hydroxyl group, a maleic acid group, etc. Among them, from the viewpoint of improving compatibility and adhesion, a polybutadiene having a vinyl group in a side chain is preferable. The copolymer has a segment skeleton formed by polymerization of butadiene in the resin, and examples thereof include styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acrylate butadiene copolymer, vinylpyridine butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, carboxylated butadiene copolymer, epoxidized butadiene copolymer, etc. Among them, from the viewpoint of improving dispersibility and heat resistance, polybutadiene copolymer, butadiene homopolymer, and styrene-butadiene copolymer are preferable.

[0038] The content of the polybutadiene elastomer is preferably 0.1 to 20 mass %, more preferably 0.5 to 15 mass %, and further preferably 3 to 15 mass %, based on the total solid mass of the resin composition.

[0039] Among these, the crosslinking agent (B) preferably contains at least one compound selected from the group consisting of triallyl cyanurate, triallyl isocyanurate, polybutadiene, and divinylbenzene, which can further increase the crosslink density during the curing reaction (crosslinking reaction) while maintaining good impregnation properties, thereby improving the heat resistance of the cured product of the resin composition.

[0040] The number average molecular weight of the crosslinking agent (B) is preferably 600 to 4,000, and more preferably 800 to 2,000. By setting the number average molecular weight of the crosslinking agent (B) to the above lower limit, the reactivity is increased and a good cured product is obtained. By setting the number average molecular weight of the crosslinking agent (B) to the above upper limit, the increase in viscosity of the resin composition can be suppressed, and good impregnation properties can be obtained. In addition, good resin flow properties can be obtained during heat molding. The number average molecular weight may be measured by a general molecular weight measurement method, and specifically, a value measured by GPC may be mentioned.

[0041] The content of the crosslinking agent (B) is preferably 1 mass % to 30 mass %, more preferably 10 mass % to 25 mass %, and further preferably 15 mass % to 25 mass %, relative to the total solid mass of the resin composition of this embodiment.

[0042] [Inorganic filler (C)] Examples of the inorganic filler (C) include silicates such as talc, calcined clay, uncalcined clay, mica, and glass; oxides such as titanium oxide, alumina, boehmite, silica, and fused silica; carbonates such as calcium carbonate, magnesium carbonate, and hydrotalcite; hydroxides such as aluminum hydroxide, magnesium hydroxide, and calcium hydroxide; sulfates or sulfites such as barium sulfate, calcium sulfate, and calcium sulfite; borates such as zinc borate, barium metaborate, aluminum borate, calcium borate, and sodium borate; nitrides such as aluminum nitride, boron nitride, silicon nitride, and carbon nitride; and titanates such as strontium titanate and barium titanate. Among these, talc, alumina, glass, silica, mica, aluminum hydroxide, and magnesium hydroxide are preferred, and silica is particularly preferred. As the inorganic filler, one of these may be used alone, or two or more of them may be used in combination.

[0043] The lower limit of the average particle size of the inorganic filler (C) is not particularly limited, but may be, for example, 0.01 μm or more, or 0.05 μm or more. This can prevent the viscosity of the thermosetting resin varnish from increasing, and improve the workability when preparing the insulating layer. The upper limit of the average particle size of the inorganic filler (C) is not particularly limited, but is, for example, preferably 5.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. This can prevent the phenomenon of sedimentation of the inorganic filler in the thermosetting resin varnish, and a more uniform resin film can be obtained.

[0044] In this embodiment, the average particle diameter of the inorganic filler (C) can be determined by measuring the particle size distribution of the particles on a volume basis using, for example, a laser diffraction particle size distribution measuring device (LA-500, manufactured by HORIBA Corporation), and determining the particle diameter (D50) at a cumulative 50%.

[0045] The inorganic filler (C) preferably contains silica particles. The silica particles may be spherical. The average particle size of the silica particles is not particularly limited, but may be, for example, 5.0 μm or less, 0.1 μm or more and 4.0 μm or less, or 0.2 μm or more and 2.0 μm or less. This can further improve the filling property of the inorganic filler (C).

[0046] The content of the inorganic filler (C) is preferably 40 to 85 mass %, more preferably 45 to 75 mass %, and further preferably 50 to 65 mass %, based on the total solid content mass of the resin composition. By making the content of the inorganic filler (C) equal to or more than the lower limit, the cured resin film can have particularly low thermal expansion and low water absorption while maintaining impregnation. On the other hand, by making the content of the inorganic filler (C) equal to or less than the upper limit, the viscosity of the resin composition can be reduced, and impregnation can be easily improved.

[0047] [Cumarone resin (D)] The coumarone resin (D) in this embodiment refers to a (co)polymer containing a coumarone residue in its skeleton structure and having an average degree of polymerization of 4 to 8, and may be a coumarone (1-benzofuran) polymer, as well as a copolymer with indene (C9H8), styrene (C8H8), α-methylstyrene, methylindene, and vinyltoluene. Among these, a coumarone-indene copolymer and a coumarone-indene-styrene copolymer are preferred.

[0048] That is, the coumarone resin (D) contains a structural unit derived from a coumarone monomer, and may have a structural unit derived from an indene monomer and a structural unit derived from another monomer. Examples of the structural unit derived from another monomer include a structural unit derived from a styrene monomer. The coumarone resin (D) may have a repeating structure of these structural units.

[0049] The structural unit derived from the indene monomer includes, for example, those represented by the following general formula (M1).

[0050] [ka]

[0051] (In general formula (M1), R 1 From R 7 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms.

[0052] The structural unit derived from the coumarone monomer includes, for example, those represented by the following general formula (M2).

[0053] [ka]

[0054] (In general formula (M2), R C is hydrogen or an organic group having 1 to 3 carbon atoms. C may be the same as or different from each other.)

[0055] The structural unit derived from the styrene-based monomer includes, for example, those represented by the following general formula (M3). [ka]

[0056] (In general formula (M3), R S is hydrogen or an organic group having 1 to 3 carbon atoms. S may be the same as or different from each other.)

[0057] In the above general formulae (M1) to (M3), R 1 From R 7 , R C and R S For example, the structure of the organic group may include atoms other than hydrogen and carbon. Specific examples of atoms other than hydrogen and carbon include oxygen atoms, nitrogen atoms, sulfur atoms, phosphorus atoms, silicon atoms, fluorine atoms, chlorine atoms, etc. The atoms other than hydrogen and carbon may include one or more of the above specific examples.

[0058] In the above general formulae (M1) to (M3), R 1 From R 7 , R C and R S are each independently, for example, hydrogen or an organic group having 1 to 3 carbon atoms, preferably hydrogen or an organic group having 1 carbon atom, and more preferably hydrogen.

[0059] In the above general formulae (M1) to (M3), 1 From R 7 , R C and R S Specific examples of the organic group constituting the formula (I) include alkyl groups such as a methyl group, an ethyl group, and an n-propyl group; alkenyl groups such as an allyl group and a vinyl group; alkynyl groups such as an ethynyl group; alkylidene groups such as a methylidene group and an ethylidene group; cycloalkyl groups such as a cyclopropyl group; and heterocyclic groups such as an epoxy group and an oxetanyl group.

[0060] The coumarone resin (D) may contain, among others, indene, a copolymer of coumarone and styrene, or a copolymer of indene and styrene, which can improve the low dielectric properties.

[0061] Furthermore, the coumarone resin (D) can improve low dielectric properties by having reactive groups such as OH groups and COOH groups. The coumarone resin (D) may have an aromatic structure having a phenolic hydroxyl group inside or at a terminal thereof.

[0062] The upper limit of the mass average molecular weight Mw of the coumarone resin (D) is, for example, preferably not more than 4000, more preferably not more than 2000, even more preferably not more than 1500, and still more preferably not more than 1200. This enhances the compatibility of the coumarone resin (D) with other resins, and enables the coumarone resin (D) to be appropriately dispersed. On the other hand, the lower limit of the mass average molecular weight Mw of the coumarone resin (D) is, for example, preferably at least 400, more preferably at least 500, even more preferably at least 550, and still more preferably at least 700. This allows the coumarone resin (D) to be appropriately dispersed in the resin composition.

[0063] The lower limit of the content of the coumarone resin (D) is, for example, 0.1 part by mass or more, preferably 0.5 part by mass or more, more preferably 1 part by mass or more, based on 100 parts by mass of the total solid content of the resin composition, which can improve the low water absorption property while obtaining a good balance between low dielectric property and impregnation property. On the other hand, the upper limit of the content of the coumarone resin (D) is, for example, 20 parts by mass or less, preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, based on 100 parts by mass of the total solid content of the resin composition, which allows for a good balance with other physical properties such as moldability and heat resistance.

[0064] The melting point of the coumarone resin (D) is preferably from 40° C. to 120° C., and the melting point can be controlled by the molecular weight and degree of polymerization.

[0065] The resin composition of the present embodiment may further contain the following components.

[0066] [Maleimide compounds] The maleimide compound of this embodiment has a bicyclic hydrocarbon group. The bicyclic hydrocarbon group refers to a residue obtained by removing one hydrogen atom from a bicyclic hydrocarbon formed of 8 to 10 carbon atoms. Specific examples include a naphthalene ring group, a dihydronaphthalene ring group, a tetrahydronaphthalene ring group, an octatetrahydronaphthalene ring group, an indene ring group, an indane ring group, and an azulene ring group. Among these, an indane ring group is preferable from the viewpoint of reducing the viscosity.

[0067] Examples of the maleimide compound having an indane ring group include those represented by the following formula (a-1).

[0068] [ka]

[0069] (In formula (a-1), Ra and Rb each independently represent any one of an alkyl group, an alkyloxy group, and an alkylthio group having 1 to 10 carbon atoms, an aryl group, an aryloxy group, and an arylthio group having 6 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, a halogen atom, a nitro group, a hydroxyl group, and a mercapto group. q represents an integer value of 0 to 4, and r represents an integer value of 0 to 3. n represents the average number of repeating units of 0.5 to 20.)

[0070] In formula (a-1), when q is 2 to 4, Ra may be the same or different in the same ring, and when r is 2 to 3, Rb may be the same or different in the same ring.

[0071] In formula (a-1), Ra is preferably any one of an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms, and more preferably an alkyl group having 1 to 4 carbon atoms. This reduces the planarity and crystallinity in the vicinity of the maleimide group while maintaining the good reactivity of the maleimide group, thereby improving the solubility in a solvent. In addition, q is preferably 2 to 3, and more preferably 2.

[0072] In formula (a-1), when r is 0, Rb is preferably a hydrogen atom, which reduces steric hindrance during the formation of the indane skeleton in the maleimide, allowing the synthesis of the maleimide to be stable. Furthermore, when r is 1 to 3, Rb is preferably at least one selected from the group consisting of an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms, and is more preferably an alkyl group having 1 to 4 carbon atoms.

[0073] The maleimide compound of the present embodiment has an indane skeleton in its structure, and thus can have improved solvent solubility compared to conventional maleimide compounds. The average number n (average value) of repeating units in the indane skeleton of formula (a-1) is preferably 0.5 to 20, more preferably 0.7 to 10.0, even more preferably 0.95 to 10.0, particularly preferably 0.98 to 9.0, even more preferably 0.99 to 8.0, even more preferably 1.0 to 7.0, and even more preferably 1.0 to 6.0. By setting the repeating unit n to be equal to or greater than the above lower limit, the proportion of high molecular weight components increases, and brittle resistance and heat resistance of the cured product can be obtained. On the other hand, by making the repeating unit n equal to or less than the upper limit, the proportion of high molecular weight components is reduced, and the solvent solubility can be improved. In addition, good flowability and handleability can be obtained.

[0074] In addition, the maleimide group in the maleimide compound has a planar structure of a five-membered ring, and the double bond of the maleimide group is highly polar and easily interacts with molecules, so that it exhibits strong intermolecular interactions with the maleimide group, benzene ring, other compounds having a planar structure, and the like, and can suppress molecular motion. Therefore, by including the maleimide compound in the resin composition of the present embodiment, the linear expansion coefficient of the obtained insulating layer can be reduced, the glass transition temperature can be improved, and further, the heat resistance can be improved.

[0075] The content of the maleimide compound is preferably from 1 mass % to 40 mass %, more preferably from 5 mass % to 35 mass %, and further preferably from 10 mass % to 20 mass %, based on the total solid content of the resin composition. By setting the content of the maleimide compound to the above lower limit, it is possible to lower the viscosity and improve the impregnation property while achieving a good dielectric tangent and a low dielectric tangent, and also to lower the linear expansion coefficient, increase the glass transition temperature, and improve the heat resistance. On the other hand, by setting the content of the maleimide compound to the above upper limit or less, it is possible to improve the balance between a good dielectric tangent, a low dielectric tangent, and impregnation properties.

[0076] [Compound (E)] The resin composition of the present embodiment may further contain a compound (E) having a skeleton of multiple aromatic ester structures and an unsaturated bond group at the end. This improves the low dielectric properties while improving the impregnation property, and suppresses unevenness that may occur in the cured product. In addition, it improves the adhesion and improves the peel strength against the metal foil described below.

[0077] Compound (E) has an aromatic ester skeleton. The aromatic ester skeleton refers to a skeleton having an ester bond and an aromatic ring bonded to one end or both ends of the ester bond. Among them, those having aromatic rings at both ends of the ester bond are preferred. Examples of groups having such a skeleton include an arylcarbonyloxy group, an aryloxycarbonyl group, an arylenecarbonyloxy group, an aryleneoxycarbonyl group, an arylcarbonyloxyarylene group, an aryloxycarbonylarylene group, an arylenecarbonyloxyarylene group, an aryleneoxycarbonylarylene group, and the like. The number of carbon atoms in the group having such a skeleton is preferably 7 to 20, more preferably 7 to 15, and even more preferably 7 to 11. The aromatic hydrocarbon group such as an aryl group and an arylene group may have a substituent.

[0078] The aryl group is preferably an aryl group having 6 to 30 carbon atoms, more preferably an aryl group having 6 to 20 carbon atoms, and even more preferably an aryl group having 6 to 10 carbon atoms. Examples of such aryl groups include those obtained by removing one hydrogen atom from a monocyclic aromatic compound such as a phenyl group, a furanyl group, a pyrrolyl group, a thiophene group, an imidazolyl group, a pyrazolyl group, an oxazolyl group, an isoxazolyl group, a thiazolyl group, an isothiazolyl group, a pyridinyl group, a pyrimidinyl group, a pyridazinyl group, a pyrazinyl group, or a triazinyl group; and those obtained by removing one hydrogen atom from a condensed ring aromatic compound such as a naphthyl group, anthracenyl group, a phenalenyl group, a phenanthrenyl group, a quinolinyl group, an isoquinolinyl group, a quinazolyl group, a phthalazinyl group, a pteridinyl group, a coumarinyl group, an indole group, a benzimidazolyl group, a benzofuranyl group, or an acridinyl group.

[0079] The arylene group is preferably an arylene group having 6 to 30 carbon atoms, more preferably an arylene group having 6 to 20 carbon atoms, and further preferably an arylene group having 6 to 10 carbon atoms. Examples of such arylene groups include a phenylene group, a naphthylene group, an anthracenylene group, and a biphenylene group.

[0080] The compound (E) contains an unsaturated bond group. The unsaturated bond may be a carbon-carbon unsaturated bond. The compound (E) preferably has at least one unsaturated bond as a substituent. Specifically, examples of the unsaturated bond include unsaturated hydrocarbon groups such as an alkenyl group having 2 to 30 carbon atoms and an alkynyl group having 2 to 30 carbon atoms. The unsaturated bond is preferably present as a substituent on the aromatic hydrocarbon group at a terminal, and more preferably present as a substituent on the aromatic hydrocarbon groups at both terminals.

[0081] Examples of the alkenyl group having 2 to 30 carbon atoms include a vinyl group, an allyl group, a propenyl group, an isopropenyl group, a 1-propenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, a 1-hexenyl group, a 2-hexenyl group, a 3-hexenyl group, a 4-hexenyl group, a 5-hexenyl group, a 1-octenyl group, a 2-octenyl group, a 1-undecenyl group, a 1-pentadecenyl group, a 3-pentadecenyl group, and a 4-pentadecenyl group. Examples of such an alkyl group include a 7-pentadecenyl group, a 1-octadecenyl group, a 2-octadecenyl group, a cyclopentenyl group, a cyclohexenyl group, a cyclooctenyl group, a 1,3-butadienyl group, a 1,4-butadienyl group, a hexa-1,3-dienyl group, a hexa-2,5-dienyl group, a pentadeca-4,7-dienyl group, a hexa-1,3,5-trienyl group, and a pentadeca-1,4,7-trienyl group.

[0082] Examples of the alkynyl group having 2 to 30 carbon atoms include an ethynyl group, a propargyl group, a 1-butynyl group, a 2-butynyl group, a 3-butynyl group, a 3-pentynyl group, a 4-pentynyl group, and a 1,3-butadiynyl group.

[0083] Among these, an alkenyl group having 2 to 30 carbon atoms is preferable, an alkenyl group having 2 to 10 carbon atoms is more preferable, an alkenyl group having 2 to 5 carbon atoms is even more preferable, an allyl group, an isopropenyl group, or a 1-propenyl group is even more preferable, and an allyl group is particularly preferable.

[0084] In addition to the aromatic ester skeleton, the compound (E) may have any of an aromatic hydrocarbon group, an aliphatic hydrocarbon group, an oxygen atom, a sulfur atom, and a group consisting of a combination thereof.

[0085] The aromatic hydrocarbon group is preferably a divalent aromatic hydrocarbon group, more preferably an arylene group or an aralkylene group, and even more preferably an arylene group. The arylene group is preferably an arylene group having 6 to 30 carbon atoms, more preferably an arylene group having 6 to 20 carbon atoms, and even more preferably an arylene group having 6 to 10 carbon atoms. Examples of such arylene groups include a phenylene group, a naphthylene group, an anthracenylene group, and a biphenylene group. The aralkylene group is preferably an aralkylene group having 7 to 30 carbon atoms, more preferably an aralkylene group having 7 to 20 carbon atoms, and even more preferably an aralkylene group having 7 to 15 carbon atoms. Among these, a phenylene group is preferable.

[0086] The aliphatic hydrocarbon group is preferably a divalent aliphatic hydrocarbon group, more preferably a divalent saturated aliphatic hydrocarbon group, and further preferably an alkylene group or a cycloalkylene group. The alkylene group is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and further preferably an alkylene group having 1 to 3 carbon atoms. Examples of the alkylene group include a methylene group, an ethylene group, a propylene group, a 1-methylmethylene group, a 1,1-dimethylmethylene group, a 1-methylethylene group, a 1,1-dimethylethylene group, a 1,2-dimethylethylene group, a butylene group, a 1-methylpropylene group, a 2-methylpropylene group, a pentylene group, and a hexylene group.

[0087] The cycloalkylene group is preferably a cycloalkylene group having 3 to 20 carbon atoms, more preferably a cycloalkylene group having 3 to 15 carbon atoms, and even more preferably a cycloalkylene group having 5 to 10 carbon atoms. Examples of the cycloalkylene group include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cyclopentylene group, a cycloheptylene group, and cycloalkylene groups represented by the following formulas (a) to (d). In the formulas (a) to (d), "*" represents a bond.

[0088] [ka]

[0089] The aromatic ester skeleton, aromatic hydrocarbon group, aliphatic hydrocarbon group, and unsaturated hydrocarbon group may have a substituent. Examples of the substituent include an unsaturated hydrocarbon group, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and a halogen atom. The substituent may be contained alone or in combination of two or more kinds.

[0090] Examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, an n-nonyl group, a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, and a cyclononyl group.

[0091] The alkoxy group having 1 to 10 carbon atoms is not particularly limited, but examples thereof include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, a pentyloxy group, a hexyloxy group, a 2-ethylhexyloxy group, an octyloxy group, and a nonyloxy group.

[0092] The halogen atom may be a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc. The above-mentioned substituent may further have a substituent. The unsaturated hydrocarbon group is as described above. The secondary substituent may be the same as the above-mentioned substituent, unless otherwise specified.

[0093] The compound (E) is preferably a compound represented by the following formula (d-1).

[0094] [ka]

[0095] (In general formula (d-1), Ar11 each independently represents a monovalent aromatic hydrocarbon group which may have a substituent, Ar 12 each independently represents a divalent aromatic hydrocarbon group which may have a substituent; Ar 13 each independently represents a divalent aromatic hydrocarbon group which may have a substituent, a divalent aliphatic hydrocarbon group which may have a substituent, an oxygen atom, a sulfur atom, or a divalent group consisting of a combination thereof. n represents an integer of 0 to 10.

[0096] In general formula (d-1), Ar 11 Each of the groups independently represents a monovalent aromatic hydrocarbon group which may have a substituent. Examples of the monovalent aromatic hydrocarbon group include monocyclic aromatic compounds such as phenyl, furanyl, pyrrolyl, thiophene, imidazolyl, pyrazolyl, oxazolyl, isoxazolyl, thiazolyl, isothiazolyl, pyridinyl, pyrimidinyl, pyridazinyl, pyrazinyl, and triazinyl, from which one hydrogen atom has been removed; and condensed aromatic compounds such as naphthyl, anthracenyl, phenalenyl, phenanthrenyl, quinolinyl, isoquinolinyl, quinazolyl, phthalazinyl, pteridinyl, coumarinyl, indole, benzimidazolyl, benzofuranyl, and acridinyl, from which one hydrogen atom has been removed. Among these, the phenyl group is preferred from the viewpoint of obtaining low dielectric properties. Ar 11 The monovalent aromatic hydrocarbon group represented by may have a substituent. The substituent is the same as the substituent that the aromatic ester skeleton may have. Among them, Ar 11 The substituent preferably contains an unsaturated bond.

[0097] In general formula (d-1), Ar 12each independently represents a divalent aromatic hydrocarbon group which may have a substituent. Examples of the divalent aromatic hydrocarbon group include an arylene group and an aralkylene group, and an arylene group is preferred. As the arylene group, an arylene group having 6 to 30 carbon atoms is preferred, an arylene group having 6 to 20 carbon atoms is more preferred, and an arylene group having 6 to 10 carbon atoms is even more preferred. Examples of such an arylene group include a phenylene group, a naphthylene group, an anthracenylene group, and a biphenylene group. As the aralkylene group, an aralkylene group having 7 to 30 carbon atoms is preferred, an aralkylene group having 7 to 20 carbon atoms is more preferred, and an aralkylene group having 7 to 15 carbon atoms is even more preferred. Among these, a phenylene group is preferred.

[0098] Ar 12 The divalent aromatic hydrocarbon group represented by may have a substituent. The substituent is the same as the substituent that the aromatic ester skeleton may have.

[0099] In general formula (d-1), Ar 13 each independently represents a divalent aromatic hydrocarbon group which may have a substituent, a divalent aliphatic hydrocarbon group which may have a substituent, an oxygen atom, a sulfur atom, or a divalent group consisting of a combination thereof, and a divalent group consisting of a combination thereof is preferable. 12 The divalent aromatic hydrocarbon group represented by the formula (I) is the same as the divalent aromatic hydrocarbon group represented by the formula (I).

[0100] As the divalent aliphatic hydrocarbon group, a divalent saturated aliphatic hydrocarbon group is more preferable, an alkylene group or a cycloalkylene group is preferable, and a cycloalkylene group is more preferable.

[0101] The alkylene group is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and further preferably an alkylene group having 1 to 3 carbon atoms. Examples of the alkylene group include a methylene group, an ethylene group, a propylene group, a 1-methylmethylene group, a 1,1-dimethylmethylene group, a 1-methylethylene group, a 1,1-dimethylethylene group, a 1,2-dimethylethylene group, a butylene group, a 1-methylpropylene group, a 2-methylpropylene group, a pentylene group, and a hexylene group.

[0102] The cycloalkylene group is preferably a cycloalkylene group having 3 to 20 carbon atoms, more preferably a cycloalkylene group having 3 to 15 carbon atoms, and even more preferably a cycloalkylene group having 5 to 10 carbon atoms. Examples of the cycloalkylene group include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cyclopentylene group, a cycloheptylene group, and cycloalkylene groups represented by the above formulas (a) to (d), and the cycloalkylene group represented by formula (c) is preferred.

[0103] As a divalent group formed from such a combination, a divalent group formed by combining a divalent aromatic hydrocarbon group which may have a substituent and a divalent aliphatic hydrocarbon group which may have a substituent is preferred, and a divalent group formed by alternately combining a plurality of divalent aromatic hydrocarbon groups which may have a substituent and a plurality of divalent aliphatic hydrocarbon groups which may have a substituent is more preferred.

[0104] Specifically, the compound may be represented by the following formula (d-2).

[0105] [ka] (In the formula, x represents 0 or an integer of 1 or more, and y represents an integer of 1 to 10.)

[0106] The mass average molecular weight of the compound (E) is preferably from 150 to 3,000, more preferably from 200 to 2,000, and even more preferably from 250 to 1,500. The weight-average molecular weight is a polystyrene-equivalent weight-average molecular weight measured by gel permeation chromatography (GPC).

[0107] The content of the compound (E) is preferably from 0.1 to 30 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1.0 to 10 mass %, based on the total solid content mass of the resin composition. By making the content of compound (E) equal to or more than the lower limit, it is possible to obtain a low dielectric tangent, improve adhesion, and improve peel strength, whereas by making the content of compound (E) equal to or less than the upper limit, it is possible to suppress an increase in viscosity and obtain good impregnation.

[0108] [Phenols with unsaturated double bonds] The resin composition of the present embodiment may further contain a phenol having an unsaturated double bond. In this embodiment, phenol having an unsaturated double bond is mainly used from the viewpoint of maintaining a balance between other physical properties while improving dielectric properties and impregnation properties. Phenol having an unsaturated double bond refers to a phenol having a phenol skeleton and an unsaturated double bond in a substituent of a benzene ring. In this embodiment, examples of phenols having an unsaturated double bond include allylphenol (o-, m- or p-), vinylphenol (o-, m- or p-), allylresorcinol, diallylresorcinol, allylcatechol, diallylcatechol, allylhydroquinone, diallylhydroquinone, allylpyrogallol, triallylphenol, trivinylphenol, triallylresorcinol, trivinylresorcinol, etc. Among them, from the viewpoint of improving adhesion, vinylphenol (particularly p-vinylphenol; 4-ethenylphenol), 2,2'-diallylbisphenol A, o-allylphenol (2-allylphenol), and allylphenol resorcinol type novolak resin are preferred.

[0109] The content of the phenol having an unsaturated double bond is preferably from 1 mass % to 30 mass %, more preferably from 5 mass % to 25 mass %, and even more preferably from 7 mass % to 22 mass %, based on the total solid content of the resin composition.

[0110] [Vinyl compounds] The resin composition of the present embodiment may further contain a vinyl compound. In the present embodiment, the vinyl compound refers to a compound having two or more polymerizable unsaturated bonds in the molecule. Examples of the vinyl compound include bifunctional aromatic vinyl compounds such as divinylbenzene and divinyltoluene; bifunctional (meth)acrylic acid esters such as 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, neopentyl glycol acrylate, allyl acrylate, neopentyl glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, 3-methylpentanediol diacrylate, and allyl methacrylate; trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, and the like. Examples of the (meth)acrylic acid esters include trifunctional or higher (meth)acrylic acid esters such as pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, pentaerythritol pentaacrylate, pentaerythritol pentamethacrylate, dipentaerythritol hexaacrylate, and dipentaerythritol hexamethacrylate; (meth)acrylic acid esters of polyhydric alcohols such as (poly)ethylene glycol dimethacrylate; diallyl maleate, diallyl fumarate, triallyl cyanurate, triallyl isocyanate, diallyl phthalate, and bis(acryloyloxyethyl) ether of bisphenol A, which can be used alone or in combination of two or more. Among these, (meth)acrylic acid esters of polyhydric alcohols such as (poly)ethylene glycol dimethacrylate; diallyl maleate, diallyl fumarate, triallyl cyanurate, triallyl isocyanate, diallyl phthalate, and bis(acryloyloxyethyl) ether of bisphenol A are preferred, with triallyl isocyanate being more preferred.

[0111] The content of the vinyl compound is preferably from 0.5 to 30% by mass, more preferably from 1 to 20% by mass, and further preferably from 4 to 15% by mass, based on the total solid content of the resin composition.

[0112] [Flame retardant] The resin composition of the present embodiment may further contain a flame retardant. In the present embodiment, examples of the flame retardant include halogen-based flame retardants such as bromine-based flame retardants and phosphorus-based flame retardants. Specific examples of the halogen-based flame retardant include bromine-based flame retardants such as pentabromodiphenyl ether, octabromodiphenyl ether, decabromodiphenyl ether, tetrabromobisphenol A, and hexabromocyclododecane, and chlorine-based flame retardants such as chlorinated paraffin. Specific examples of the phosphorus-based flame retardant include phosphate esters such as condensed phosphate esters and cyclic phosphate esters, phosphazene compounds such as cyclic phosphazene compounds, phosphinate-based flame retardants such as phosphinic acid metal salts such as dialkylphosphinic acid aluminum salts, melamine-based flame retardants such as melamine phosphate and polymelamine phosphate. As the flame retardant, each of the exemplified flame retardants may be used alone or in combination of two or more. Among these, phosphorus-based flame retardants are preferred.

[0113] The content of the flame retardant is preferably from 0.1 to 15% by mass, more preferably from 0.5 to 10% by mass, and even more preferably from 1 to 5% by mass, based on the total solid content of the resin composition.

[0114] [Polymerization initiator] The resin composition of the present embodiment may contain a polymerization initiator. This allows the curing to proceed stably. The polymerization initiator is not particularly limited as long as it can accelerate the curing reaction between the modified polyphenylene ether and the thermosetting curing agent, and examples thereof include oxidizing agents such as 1,3-di(t-butylperoxy-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, benzoyl peroxide, 3,3',5,5'-tetramethyl-1,4-diphenoquinone, chloranil, 2,4,6-tri-t-butylphenoxyl, t-butylperoxyisopropyl monocarbonate, and azobisisobutyronitrile. These may be used alone or in combination of two or more. In addition, from the viewpoint of further accelerating the curing reaction, a carboxylate metal salt or the like may be used in combination. Among them, α,α'-bis(t-butylperoxy-m-isopropyl)benzene is preferably used. α,α'-bis(t-butylperoxy-m-isopropyl)benzene has a relatively high reaction initiation temperature, and therefore can suppress the promotion of the curing reaction at a time when curing is not required, such as when drying the prepreg, and can suppress the deterioration of the storage stability of the resin composition of this embodiment. Furthermore, α,α'-bis(t-butylperoxy-m-isopropyl)benzene has low volatility, so it does not volatilize during drying or storage of the prepreg, and good stability can be obtained.

[0115] [Coupling agent] The resin composition of the present embodiment may contain a coupling agent. The coupling agent may be added directly when preparing the resin composition, or may be added in advance to the inorganic filler (C). The use of the coupling agent can improve the wettability of the interface between the inorganic filler (C) and each resin. Therefore, it is preferable to use a coupling agent, and the heat resistance of the cured resin film can be improved. In addition, the use of the coupling agent can improve the adhesion to the copper foil. Furthermore, since the moisture absorption resistance can be improved, the adhesion to the copper foil can be maintained even in a humid environment.

[0116] The above-mentioned coupling agent may be, for example, a silane coupling agent such as a vinyl-based silane coupling agent, an epoxy silane coupling agent, a cationic silane coupling agent, or an amino silane coupling agent, a titanate-based coupling agent, or a silicone oil-type coupling agent. The coupling agent may be used alone or in combination of two or more kinds. In this embodiment, the coupling agent may contain a silane coupling agent. This makes it possible to increase the wettability at the interface between the inorganic filler (C) and each resin, and further improve the heat resistance of the cured resin film.

[0117] As the silane coupling agent, various types can be used, and examples thereof include epoxy silane, amino silane, alkyl silane, ureido silane, mercapto silane, vinyl silane, and the like.

[0118] Specific examples of the compounds include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-phenylγ-aminopropyltriethoxysilane, N-phenylγ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-6-(aminohexyl)3-aminopropyltrimethoxysilane, N-(3-(trimethoxysilylpropyl)-1,3-benzenedimethanane, γ-glycidoxypropanol, and the like. Examples of the silane include vinyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, methyltrimethoxysilane, γ-ureidopropyltriethoxysilane, vinyltriethoxysilane, etc., and one or more of these can be used in combination. Among these, vinylsilane, epoxysilane, mercaptosilane, and aminosilane are preferred, and as the aminosilane, primary aminosilane or anilinosilane is more preferred.

[0119] The content of the coupling agent can be appropriately adjusted based on the specific surface area of ​​the inorganic filler (C). The lower limit of the content of the coupling agent can be, for example, 0.01 mass% or more, preferably 0.05 mass% or more, based on the total solid content of the resin composition. When the content of the coupling agent is equal to or more than the lower limit, the inorganic filler (C) can be sufficiently covered, and the heat resistance of the cured resin film can be improved. On the other hand, the upper limit of the content of the coupling agent may be, for example, 3 mass % or less, preferably 1.5 mass % or less, based on the total solid content of the resin composition. When the content of the coupling agent is equal to or less than the upper limit, it is possible to suppress the effect on the reaction and to suppress the decrease in bending strength, etc. of the cured resin film.

[0120] [others] The resin composition of the present embodiment may contain additives other than the above-mentioned components, such as resins other than those mentioned above, dyes such as green, red, blue, yellow, and black, pigments such as black pigments, colorants including one or more selected from the group consisting of dyes, stress reducing agents, antifoaming agents, leveling agents, adhesion aids, ultraviolet absorbers, foaming agents, antioxidants, ion scavengers, rubber components, etc., within the scope of the present invention. These may be used alone or in combination of two or more. Examples of resins other than those mentioned above include thermosetting resins such as epoxy resins and benzocyclobutene resins, thermoplastic resins, phenoxy resins, and cyanate resins.

[0121] (Varnish-like resin composition) The resin composition of the present embodiment can be in the form of a varnish further containing a solvent. Since the resin composition of the present embodiment contains the above-mentioned components, it is possible to produce a varnish with a low viscosity. As a result, it is possible to improve the impregnation into the substrate and the workability. In addition, it is possible to improve the adhesion.

[0122] Examples of the solvent include organic solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, toluene, mesitylene, ethyl acetate, cyclohexane, heptane, cyclohexane, cyclohexanone, tetrahydrofuran, dimethylformamide, dimethylacetamide, dimethylsulfoxide, ethylene glycol, ethylene glycol ether, cellosolves, carbitols, anisole, and N-methylpyrrolidone. These may be used alone or in combination of two or more. Among them, from the viewpoint of reducing the change in peel strength, toluene, heptane, cyclohexane, anisole, and mesitylene are preferable, toluene is more preferable, and it is even more preferable to contain at least 5% or more of toluene. These solvents have excellent solubility and compatibility with the above resins, so that the change in peel strength can be reduced. In addition, the solvent can be dried efficiently. From the viewpoint of promoting compatibility and adhesion with the inorganic filler (C) such as silica and reducing changes in peel strength, it is preferable to use methyl isobutyl ketone, cyclohexanone, or ethylene glycol ether.

[0123] When the resin composition is in the form of a varnish, the solid content of the resin composition may be, for example, 30% by mass or more and 80% by mass or less, more preferably 40% by mass or more and 70% by mass or less, which results in a resin composition with excellent workability and film-forming properties.

[0124] The varnish-like resin composition can be prepared by dissolving, mixing, and stirring the above-mentioned components in a solvent using various mixers such as those used in an ultrasonic dispersion system, a high-pressure collision dispersion system, a high-speed rotation dispersion system, a bead mill system, a high-speed shear dispersion system, and a rotation-revolution dispersion system.

[0125] <Resin film> Next, the resin film of this embodiment will be described. The resin film of this embodiment can be obtained by forming the above-mentioned resin composition in a varnish form into a film. For example, the resin film of this embodiment can be obtained by removing the solvent from a coating film obtained by applying the resin composition in a varnish form. In such a resin film, the solvent content can be 5 mass % or less with respect to the entire resin film. In this embodiment, the step of removing the solvent may be carried out under conditions of, for example, 100°C to 150°C and 1 minute to 5 minutes. This makes it possible to sufficiently remove the solvent while suppressing the progress of curing of the resin film containing a thermosetting resin.

[0126] The resin film of the present embodiment may be composed of a resin film alone, or may be composed so as to include a fiber base material therein.

[0127] <Prepreg> The prepreg of this embodiment is obtained by impregnating a fiber substrate with the resin composition. For example, the prepreg can be used as a sheet-like material obtained by impregnating a fiber substrate with the resin composition and then semi-curing it. The sheet-like material having such a structure is excellent in various properties such as dielectric properties and mechanical and electrical connection reliability under high temperature and humidity, and is suitable for manufacturing an insulating layer of a printed wiring board, for example.

[0128] In this embodiment, the method of impregnating the resin composition into the fiber substrate is not particularly limited, but examples thereof include a method of dissolving the resin composition in a solvent to prepare a resin varnish and immersing the fiber substrate in the resin varnish, a method of applying the resin varnish to the fiber substrate using various coaters, a method of spraying the resin varnish onto the fiber substrate using a sprayer, and a method of laminating both sides of the fiber substrate with the resin film consisting of the resin composition.

[0129] Examples of the fiber substrate include glass fiber substrates such as woven glass cloth and nonwoven glass cloth, inorganic fiber substrates such as woven or nonwoven cloth containing inorganic compounds other than glass as components, and organic fiber substrates composed of organic fibers such as aromatic polyamideimide resin, polyamide resin, aromatic polyester resin, polyester resin, polyimide resin, and fluororesin, etc. Among these substrates, the use of a glass fiber substrate typified by glass woven cloth in terms of strength can improve the mechanical strength and heat resistance of the printed wiring board.

[0130] The thickness of the fiber base material is not particularly limited, but is preferably 5 μm to 150 μm, more preferably 10 μm to 100 μm, and even more preferably 12 μm to 90 μm. By using a fiber base material having such a thickness, the handleability during the production of the prepreg can be further improved. When the thickness of the fiber substrate is equal to or less than the upper limit, the impregnation of the resin composition in the fiber substrate is improved, and the occurrence of strand voids and a decrease in insulation reliability can be suppressed. When the thickness of the fiber substrate is equal to or more than the lower limit, the strength of the prepreg using the fiber substrate can be improved.

[0131] As the above-mentioned glass fiber substrate, for example, a glass fiber substrate formed of one or more types of glass selected from E glass, S glass, D glass, T glass, NE glass, UT glass, L glass, HP glass and quartz glass is suitably used.

[0132] In this embodiment, the prepreg can be used to form, for example, an insulating layer in a build-up layer or an insulating layer in a core layer of a printed wiring board. When the prepreg is used to form an insulating layer in a core layer of a printed wiring board, for example, two or more prepregs can be stacked and the resulting laminate can be heat-cured to form an insulating layer for the core layer.

[0133] The thickness of the prepreg is not particularly limited, but is preferably 5 μm or more and 150 μm or less, more preferably 10 μm or more and 100 μm or less, and further preferably 12 μm or more and 90 μm or less. When the thickness of the prepreg is equal to or less than the upper limit, it is easy to form through-holes using carbon dioxide gas, UV, excimer or other lasers. When the thickness of the prepreg is equal to or more than the lower limit, the strength of the prepreg can be improved. As a result, the handling properties can be improved, the prepreg can be easily produced, and warping of the resin substrate can be suppressed.

[0134] <Metal-clad laminate> The laminate of the present embodiment is a metal-clad laminate in which a metal layer is disposed on at least one surface of the cured product of the prepreg.

[0135] A method for producing a metal-clad laminate using a prepreg is, for example, as follows. A metal foil is placed on both the upper and lower sides or one side of the outer side of a prepreg or a laminate of two or more prepregs, and these are bonded under high vacuum conditions using a laminator or Becquerel device, or a metal foil is placed on both the upper and lower sides or one side of the outer side of the prepreg as is. When two or more prepregs are laminated, a metal foil is placed on both the upper and lower sides or one side of the outermost side of the laminated prepregs. Next, a metal-clad laminate can be obtained by hot-press molding the laminate of the prepreg and the metal foil. Here, it is preferable to continue pressing until the end of cooling during hot-press molding.

[0136] Examples of the metals constituting the metal foil include copper, copper-based alloys, aluminum, aluminum-based alloys, silver, silver-based alloys, gold, gold-based alloys, zinc, zinc-based alloys, nickel, nickel-based alloys, tin, tin-based alloys, iron, iron-based alloys, Fe-Ni-based alloys such as Kovar (trade name), 42 alloy, Invar, and Super Invar, W, and Mo. Among these, the metal constituting the metal foil 105 is preferably copper or a copper alloy, because it has excellent conductivity, is easy to form a circuit by etching, and is inexpensive. That is, the metal foil is preferably copper foil. As the metal foil, a metal foil with a carrier or the like can also be used. The thickness of the metal foil is preferably 0.5 μm or more and 20 μm or less, and more preferably 1.5 μm or more and 18 μm or less.

[0137] <Wiring board> In this embodiment, the wiring board is a board having a conductor layer on one or both sides of a base material with metal foil, the conductor layer having a circuit formed by etching the metal foil into a desired pattern, etc. This allows the board to be used as a wiring board on which miniaturized and highly dense components are mounted. The wiring board of the present embodiment may also include a microstrip line including a microstrip line formed by etching a metal foil. Moreover, various pads, vias, and patterns are added to an antenna or device circuit using the wiring board of this embodiment.

[0138] The above etching can be performed by chemical etching (wet etching), and the etching solution can be a copper chloride solution, nitric acid, or the like, or can be performed by a method using other acidic solutions, alkaline solutions, or the like. The bonding with the metal foil can be carried out by a known method. For example, the adhesive film and the metal foil can be bonded by continuous processing using a hot roll laminator having one or more pairs of metal rolls or a double belt press (DBP). Since the device configuration is simple and advantageous in terms of maintenance costs, the bonding of the adhesive film and the metal foil is preferably carried out by thermal lamination using a hot roll laminator having one or more pairs of metal rolls.

[0139] The wiring board of the present embodiment may be used in a high frequency band of microwaves, for example, 10 GHz to 100 GHz. In particular, by using a frequency band of 60 GHz or more, the moisture absorption suppression effect can be effectively obtained, and high reliability can be obtained.

[0140] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES

[0141] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.

[0142] (1) Synthesis of resin (A) [Synthesis of resin (A-1)] First, p-toluenesulfonic acid (7.61 g, 40 mmol) was used as an acid catalyst, and 3-mercaptopropionic acid (0.212 g, 2 mmol) was used as a co-catalyst. 4-phenoxyphenol (6.7 g, 36 mmol), p-tolualdehyde (9.6 g, 80 mmol), and diphenyl ether (14.3 g, 84 mmol) were mixed, and the mixture was refluxed at 130°C for 4 hours in a toluene solvent (35 ml). After neutralization with an aqueous solution of sodium hydroxide (NaOH), a solution of resin (a-1) was obtained as an intermediate. Next, the obtained resin (a-1) solution was reacted with chloromethylstyrene (12.1 g, 79.4 mmol), sodium hydroxide (NaOH) aqueous solution (40%, 7.9 ml), and tetrabutylammonium bromide (TBABr, 4.8 g) at 75°C for 4 hours to modify the hydroxyl groups with styrene. After that, it was neutralized with 10% hydrochloric acid, and the upper layer solution was dropped into a large amount of MeOH to obtain 15.3 g of resin (A-1) containing a structural unit represented by the following formula (A-1). The average weight molecular weight was 1700, and the ratio of repeating units m and n (m:n) was 7:3.

[0143] [ka]

[0144] [Synthesis of resin (A-2)] First, p-toluenesulfonic acid (7.61 g, 40 mol) was used as an acid catalyst and 3-mercaptopropionic acid (0.212 g, 2 mol) was used as a co-catalyst, and 4-phenoxyphenol (19.37 g, 104 mol) and p-tolualdehyde (9.6 g, 80 mmol) were mixed and refluxed at 130°C for 4 hours in a toluene solvent (27 ml) to obtain an intermediate resin (a-2). Next, the obtained resin (a-2) was reacted with chloromethylstyrene (63.2g, 413.8mmol), sodium hydroxide (NaOH) aqueous solution (40%, 41.3ml), and tetrabutylammonium bromide (TBABr, 16.6g) at 75°C for 4 hours to styrene-modify the hydroxyl groups. After that, it was neutralized with 10% hydrochloric acid, and the upper layer solution was dropped into a large amount of MeOH to styrene-modify the hydroxyl groups, thereby obtaining 25.3g of resin (A-2) containing a constitutional unit represented by the following formula (A-2). The average weight molecular weight was 2700.

[0145] [ka]

[0146] [Synthesis of resin (A-3)] First, p-toluenesulfonic acid (23.78 g, 125 mmol) was used as an acid catalyst, and 3-mercaptopropionic acid (0.66 g, 6.25 mmol) was used as a co-catalyst. 2-(2-hydroxyphenyl)benzoxazole (10.6 g, 50 mmol) and p-tolualdehyde (9.6 g, 80 mmol) were mixed, and the mixture was refluxed at 130°C for 7 hours in a toluene solvent (27 ml) to obtain an intermediate resin (a-3). Next, the obtained resin (a-3) was reacted with chloromethylstyrene (63.2g, 413.8mmol), sodium hydroxide (NaOH) aqueous solution (40%, 41.3ml), and tetrabutylammonium bromide (TBABr, 15.2g) at 75°C for 4 hours to modify the hydroxyl groups with styrene. After that, it was neutralized with 10% hydrochloric acid, and the upper layer solution was dropped into a large amount of MeOH to obtain 10.4g of resin (A-3) containing a structural unit represented by the following formula (A-3). The average weight molecular weight was 1600.

[0147] [ka]

[0148] (2) Analysis and characteristics of resin (A) The synthesized resins (A-1), (A-2), and (A-3) were subjected to GPC measurement to measure the weight average molecular weight (Mw) and number average molecular weight (Mn). The results are shown in Table 1. In addition, resins (A-1), (A-2), and (A-3) all showed a phenol-derived OH peak (3500 cm) by FT-IR measurement. -1 It was confirmed that the styrene modification caused the 1 The introduction of a styrene moiety was confirmed by 1 H NMR measurement. The results are shown in Figures 1 to 6. Figure 1 shows the structure of the resin (A-1) synthesized in the example. 1 FIG. 2 is an infrared absorption spectrum of the resin (A-1) synthesized in the example, and FIG. 3 is an H-NMR spectrum of the resin (A-2) synthesized in the example. 1 FIG. 4 is an infrared absorption spectrum of the resin (A-2) synthesized in the example, and FIG. 5 is an H-NMR spectrum of the resin (A-3) synthesized in the example. 1 FIG. 6 is an H-NMR spectrum of the resin (A-3) synthesized in the example.

[0149] [Table 1]

[0150] GPC measurement conditions Tosoh gel permeation chromatography device HLC-8320GPC Column: Tosoh TSK-GEL Supermultipore HZ-M Detector: RI detector for liquid chromatography Measurement temperature: 40℃ Solvent: THF Sample concentration: 2.0 mg / ml

[0151] · 1 H NMR measurement conditions Nuclear magnetic resonance spectrometer JNM-AL300 (manufactured by JEOL) Solvent: CDCl3 Sample concentration: 3wt%

[0152] FT-IR measurement conditions Thermo Fisher Nicolet Summit Measurement method: ATR method

[0153] (3) Preparation of low dielectric resin composition Using the following raw materials, each component was dissolved or dispersed at the solid content ratio shown in Table 2, and the mixture was adjusted to 15 mass% toluene and 15 mass% methyl ethyl ketone so that the non-volatile content was 70 mass%, and then stirred using a high-speed stirrer to prepare a varnish-like resin composition (Resin Varnish P).

[0154] [Raw materials] Resin (A) or oligomer Resins (A-1) to (A-3) obtained by the above "(1) Synthesis of Resin (A)" Maleimide compound having a bicyclic hydrocarbon group: a maleimide compound obtained by Synthesis Example 1 below. Modified polyphenylene ether copolymer: Polyphenylene ether modified with terminal methacrylic groups, "SA9000" manufactured by SABIC Innovative Plastics Crosslinker (B): Crosslinking agent (B-1): Triallyl isocyanate, "TAIC" manufactured by Mitsubishi Chemical Corporation Crosslinking agent (B-2); liquid polybutadiene, "Ricon 100" manufactured by Cray Valley others Inorganic filler (C): Silica particles, "SC4050", manufactured by Admatechs Co., Ltd. (average particle size 1.1 μm, surface treated with aminophenylsilane) Coumarone resin (D): Indene-coumaron-styrene copolymer containing phenol groups at the ends (Nihon To Chemical Industry Co., Ltd., V-120S, mass average molecular weight: 950, hydroxyl value: 30 mg KOH / g) Polymerization initiator: 1,3-di[(t-butylperoxy)isopropyl]benzene "Perbutyl P" manufactured by NOF Corporation

[0155] [Synthesis Example 1: Maleimide Compound] A methyl ethyl ketone solution (70% by mass of non-volatile components) of a maleimide compound synthesized according to the description of Synthesis Example 1 described in the Japan Institute of Invention and Innovation Disclosure Technical Journal No. 2020-500211 was prepared. The obtained maleimide compound has the following structure. The FD-MS spectrum of the maleimide compound had peaks at M+=560, 718, and 876, which corresponded to n1 being 0, 1, and 2, respectively. The maleimide compound was analyzed by GPC, and the value of the number of repeating units n1 of the indane skeleton portion was calculated based on the number average molecular weight, giving n1=1.47 and a molecular weight distribution (Mw / Mn)=1.81. Furthermore, the content of maleimide compounds having an average number of repeating units n1 of 0 was 26.5 area % in the total amount of maleimide compounds (100 area %).

[0156] [ka]

[0157] (4) Preparation of prepreg The obtained resin varnish P was applied to a glass woven fabric (cloth type #1078, NE glass, basis weight 44 g / m 2 The prepreg was obtained by impregnating the mixture with the mixture using a coating device and drying it for 5 minutes using a hot air dryer at 130° C. The thickness (μm) of the obtained prepreg is shown in Table 2.

[0158] (5) Preparation of laminated plate with metal foil Ultra-thin copper foil (Mitsui Mining & Smelting Co., Ltd., Microthin FL, 1.5 μm) was laminated on both sides of each prepreg, and the laminate was heated and press-molded at a pressure of 3 MPa and a temperature of 225° C. for 2 hours to obtain a laminate with metal foil.

[0159] (6) Measurement and evaluation ·Dielectric constant, dielectric tangent The resin plate from which the extremely thin copper foil on the outermost layer of the obtained metal foil laminate had been removed was subjected to measurement of the dielectric constant and dielectric loss tangent using a 10 GHz cavity resonator. The results are shown in Table 2.

[0160] Glass transition temperature (Tg) The dynamic viscoelasticity measurement was performed using a dynamic viscoelasticity device in accordance with JIS C-6481 (DMA method). The resin plate used was made by removing the ultra-thin copper foil from the outermost layer of the metal foil laminate. A test piece measuring 8 mm x 40 mm was cut out from the resin plate obtained, and the dynamic viscoelasticity measurement was performed on the test piece at a heating rate of 5°C / min and a frequency of 1 Hz. The glass transition temperature was determined as the temperature (° C.) at which the loss tangent tan δ was at its maximum value. The results are shown in Table 2.

[0161] Linear expansion coefficient The linear expansion coefficient was measured by preparing a 4mm x 20mm test piece using a TMA (thermomechanical analysis) device (TA Instruments, Q400) and measuring the linear expansion coefficient (CTE) (ppm / ℃) at 50-100℃ in the second cycle under the conditions of a temperature range of 30-300℃, 10℃ / min, and a load of 5g. The sample used was a laminate with metal foil that had been etched to remove the copper. The results are shown in Table 2.

[0162] [Table 2]

Claims

1. A resin (A) having a repeating unit including a structure represented by the following formula (1) (excluding polystyrene resins), A crosslinking agent (B); A low dielectric resin composition comprising: 【Chemistry 1】 (In formula (1), R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and * represents a bond.

2. The low dielectric resin composition according to claim 1, A low dielectric resin composition, wherein the resin (A) has a weight average molecular weight (Mw) of 200 to 10,000.

3. The low dielectric resin composition according to claim 1 or 2, The content of the resin (A) is 1.0 mass % to 30 mass % based on the total solid mass of the low dielectric resin composition.

4. The low dielectric resin composition according to claim 1 or 2, A low dielectric resin composition, wherein resin (A) has any repeating unit selected from the following formulas (2-1) to (2-3): 【Chemistry 2】 (Wherein, R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and m and n each represent an integer of 1 to 36. 【Chemistry 3】 (Wherein, R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and l represents an integer of 1 to 26. 【Chemistry 4】 (Wherein, R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and s represents an integer of 1 to 12.

5. The low dielectric resin composition according to claim 1 or 2, The low dielectric resin composition, wherein the crosslinking agent (B) is one or more selected from the group consisting of a trialkenyl cyanurate compound, a polyfunctional vinyl compound, a vinylbenzyl compound, a polyfunctional maleimide compound, and an isocyanate compound.

6. The low dielectric resin composition according to claim 1 or 2, The low dielectric resin composition further comprises an inorganic filler (C).

7. The low dielectric resin composition according to claim 1 or 2, The content of the inorganic filler (C) is 40% by mass to 85% by mass based on the total solid content mass of the low dielectric resin composition.

8. The low dielectric resin composition according to claim 1 or 2, The low dielectric resin composition further comprises a coumarone resin (D).

9. A prepreg formed by impregnating a fiber base material with the low dielectric resin composition according to claim 1 or 2.

10. The prepreg according to claim 9, The prepreg, wherein the fiber base material is one or more types selected from the group consisting of a glass fiber base material, a polyamide resin fiber, a polyester resin fiber, a polyimide resin fiber, and a fluororesin fiber.

11. A laminate comprising the prepreg according to claim 9 and a metal layer disposed on at least one surface of the prepreg.

12. A wiring board using the prepreg according to claim 9.

13. A resin having a repeating unit containing a structure represented by the following formula (1) (excluding polystyrene resins). 【Chemistry 5】 (Wherein, R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and * represents a bond.

14. The resin according to claim 13 . A resin having an average weight molecular weight (Mw) of 200 to 10,000.

15. The resin according to claim 13 or 14, A resin having a repeating unit selected from the following formulas (2-1) to (2-3). 【Chemistry 6】 (Wherein, R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and m and n each represent an integer of 1 to 36. 【Chemistry 7】 (Wherein, R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and l represents an integer of 1 to 26. 【Chemistry 8】 (Wherein, R1 is CH or C(CH 3 ), R2 represents either hydrogen or a methyl group, and s represents an integer of 1 to 12.

Citation Information

Patent Citations

  • Laminated film, flexible metal-clad laminate, and method for producing flexible metal-clad laminate

    JP2023001060A

  • Curable resin composition

    JP2023034824A